Stochastische Simulation großflächiger, hochwasserrelevanter Niederschlagsereignisse - Ehmele, Florian Tim (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2018)
The risk estimation of precipitation events with high recurrence periods is difficult due to the limited time scale with meteorological observations. A homogenous distribution of rain gauges, especially in mountainous terrain, is also hardly convertible. In this study an analytical model with a high spatial resolution, designed for stochastic simulations of flood-related precipitation, is developed, evaluated and applied to different investigation areas in Germany.